Strengthening of the values of respect, self-esteem, tolerance and responsibility in students at the la playa headquarters. - Ochoa Díaz, July Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Introduction: The research is based on the formation in values of respect, tolerance, responsibility and self-esteem in the students of the headquarters la playa of the agricultural technical educational institution of Paipa. Methodology: the study is developed in the qualitative approach and type of action research according to the contributions of the research line of development in the classroom - school where they are represented in proposed phases. Results: an observation was made where the research problem can be known and through a semi-structured interview applied to the students and the teacher about the knowledge of values. a didactic strategy is designed for the students of the la playa headquarters which consists of four workshops, where each one of them is based on the strengthening of the values of respect, tolerance, self-esteem and responsibility. The incidence of the didactic proposal is evaluated through an evaluation of the acceptance of the workshops and this with the purpose of a field diary analyzing the results obtained. Conclusions: didactics is a way of applying in the areas where it is focused and interpreted in the teaching and learning process. By designing and applying the didactic strategy taking into account the Escuela Nueva model in the students of the La Playa school, significant changes were generated in the development and strengthening of values.